Development of an Objective Measure of Cognitive Workload for Rehabilitation Using Electroencephalography (EEG) - Ghani, Usman (Auckland University of Technology, 2022)
The purpose of rehabilitation following a neurological injury is to reduce impairments, maximize functional abilities, and enhance quality of life. As a part of rehabilitation, patient is assigned a rehabilitation task, and literature suggests this task should be challenging enough to stimulate motor learning and speed up recovery. The challenge level of a rehabilitation task is determined by variables such as the number of repetitions and the intensity of the task. Therefore, it is important for clinicians to consider these variables when setting rehabilitation programs so they can determine how challenging a rehabilitation task is for each individual. This can also help identify the optimal number of repetitions of the task, and the induced cognitive workload to achieve good rehabilitation outcomes for each patient. In current rehabilitation settings, clinicians lack a clear method to determine how challenging a task is for patients, so they monitor their performance metrics such as task completion rate, response time, and accuracy to adjust task difficulty and induced cognitive workload. Such observation method lacks sensitivity to cognitive workload variations during the task and is prone to human error. This can result in a task difficult enough to induce cognitive overload or easy enough to induce cognitive underload, both of which are detrimental to people with brain injuries and need to be avoided. Therefore, clinicians should be provided with a precise objective method for observing cognitive workload variations during rehabilitation, which may assist clinical observations in making informed decisions about task difficulty and induced cognitive workload. The aim of this thesis is to provide a framework for selecting and implementing such an objective cognitive workload evaluation method that is appropriate for rehabilitation. In this thesis, preliminary research was conducted to compare different cognitive workload evaluation methods to highlight their objectiveness. This comparison was based on several parameters such as intrusion, applicability, sensitivity, mobility, and diagnostic power. Based on this comparison, electroencephalogram (EEG)-based event-related potentials (ERPs) were identified as the most suitable method for objectively evaluating cognitive workload. This led to a narrative synthesis of ERP-based cognitive workload evaluation methods which identified key parameters that could influence such methods. Furthermore, this review compared two different types of ERP-based methods, including single-task and dual-task methods, and highlighted single-task ERP-based methods as being more suitable for rehabilitation. However, a limitation of these methods, particularly habituation of the task and stimulus, was also identified in this review. An experimental study was conducted to validate single-task ERP-based methods to measure cognitive workload by minimizing the effects of habituation. The participants were presented with three difficulty levels of a custom tilt-ball game at random for short periods in anticipation to distribute the effect of habituation across difficulty levels. According to the results, the N1 ERP component amplitude decreased with increasing difficulty and induced cognitive workload, which was in line with the previous literature. This validates the proposed single-task ERP paradigm for measuring cognitive workload despite habituation effects. A second experimental study was conducted to implement the proposed single-task ERP-based cognitive workload evaluation method in a rehabilitation-like task. The results of second experimental study confirmed the earlier finding that attention orienting response (highlighted by the N1 ERP component) decreased with increasing cognitive workload. Since the task was closer to a rehabilitation task and was more dynamic in nature, the positive results demonstrated the robustness of the proposed single-task ERP-based method for actual rehabilitation tasks. Such a method can help clinicians to gain insight into changes in cognitive workload which can be used to optimize rehabilitation.